AI-Augmented Approaches to Creative Problem-Solving: A Metacognitive Perspective - Christian Hoßbach; Scott~G. Isaksen (Creativity and Innovation Management, 2025)
Generative artificial intelligence (GenAI) is transforming the way people approach creative problem-solving (CPS). Whereas previous technologies were only used as creativity tools, GenAI can also be conceived as an actor taking on different roles that adds a collaborative element to individual CPS processes. So far, research on augmenting CPS with GenAI has focused on creative cognition. In this article, we use a metacognitive perspective as a unique lens to conceptualize AI-augmented approaches to CPS and explore the implications of AI-augmented creative cognition. Based on this, we propose that the collaboration with GenAI in CPS shifts a part of human attention away from executing to monitoring and controlling creative cognition. These imposed metacognitive demands have important implications for our theoretical understanding of AI-augmented CPS and how people can better actualize the creative potential of GenAI. Future research directions and empirical approaches for understanding and addressing these metacognitive demands are discussed along with practical implications for applying CPS.
Keywords: 330; AI-augmentation; artificial intelligence; convergent thinking; creative problem-solving; creativity; divergent thinking; GenAI; human–machine interaction; metacognition